Analisis Etos Kerja Islami Dalam Meningkatkan Kinerja Karyawan Pada Pondok Pesantren Fathul Ulum Di Kecamatan Tebing Tinggi Kabupaten Tanjung Jabung Barat - Azzuratul Nissa; Mohammad Orinaldi; Faturahman Faturahman (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Work ethic is a philosophy of life based on a view of human life that becomes a habit and is reflected in behavior and actions. Islamic work ethic should be owned and applied by a Muslim. In the Islamic work ethic emphasizes more on cooperation at work. Implementing an Islamic work ethic is very important in an agency in order to produce superior quality human resources and will later affect optimal performance at work. What happens now is that employees and teachers at Fathul Ulum Islamic Boarding School have not fully implemented the Islamic work ethic properly. There are still employees who are less responsible and less disciplined in carrying out their work. So that the application of Islamic work ethic owned by these employees has not been able to improve employee performance because the resulting performance is not optimal. The purpose of this research is to find out the Islamic work ethic applied by employees at Fathul Ulum Islamic Boarding School and whether the Islamic work ethic applied can improve employee performance. In this study using qualitative methods with a descriptive approach. The data collection techniques used are observation, interviews, and documentation. The data analysis method used is data collection, data reduction, data presentation, and conclusion drawing. he results of this study indicate that the Islamic work ethic applied by employees at Fathul Ulum Islamic Boarding School has not been fully implemented so that the resulting performance is less than optimal and certainly not effective and efficient in improving employee performance. In the future, it is hoped that the Islamic work ethic can be fully implemented by all employees at Fathul Ulum Islamic Boarding School in order to produce optimal performance and improve employee performance.